Reformasi Pengadaan Lahan Pembangunan Infrastruktur Melalui SPAT sebagai Upaya Meminimalisir Kesenjangan Pembangunan Infrastruktur Antar Wilayah di Indonesia - Guardino Ibrahim Fahmi; Fazal Akmal Musyarri (Jurnal Hukum Lex Generalis, 2020)
Land acquisition is a problem that affects infrastructure development in Indonesia. Various issues about land acquisition can hinder economic development and add to the development gap in Indonesia. Various efforts have been made by the Government to continue to support and succeed the land acquisition program. The problem that is often faced in the land procurement process is land disputes in addition to legal disputes. Various disputes that exist have the potential to hamper the construction of an infrastructure project, even not infrequently the infrastructure project becomes abandoned for many years. This is where the further enforcement of Law No. 2 of 2012 on Land Procurement for Development in the Public Interest is expected to be a means of smooth land procurement process for development in the public interest, especially infrastructure. According to the law a quo, the procurement of land for infrastructure is determined by the Governor through a decree to designate a region as infrastructure development land. If there are objections, then there will be a lawsuit to PTUN. If there is the remaining land procurement that has not been released, it will return to the initial administrative cycle. This certainly makes the resolution of disputes longer and complicated so that it seems less effective. What's more, if an infrastructure to be built is a strategic government project. So that the author initiated a grand design in the form of an Integrated Agrarian Justice System that collaborates several legal realms, considering that agrarian law is difficult to categorize into the realm of civil, criminal, and admimistration law. The handling of agrarian law cannot be handled through the current event law, so it requires a more specialized and unified event law. The research method used is normative juridical, using a statutory approach and a concept approach. SPAT is a special integrated judicial system for adjudicating disputes in the field of agrarian law, which not only uses positive laws in laws and regulations, but also accommodates applicable customary laws. SPAT is implemented through the Agrarian Court by empowering special judges of agrarian law ecstasy. In agrarian disputes, especially the preparation of land procurement for land to be built infrastructure, the government applied for land determination. Then the court proved by conducting an empirical review of the land to be designated as infrastructure land. Because it applies to the community and indigenous peoples, so that the law used is not only a positive law but also the law that applies in the community of an area.